Improvement of Shear Strength of Clay Shale Soil using Polymer-Calcite Precipitation (PCP) as Soil Stabilization Technique - Ramadhan, Fathur; Fauzan, Muhammad; Putra, Heriansyah; Sudibyo, Tri (Civil Engineering Dimension, 2025)
Clay shale is an expansive soil owing to its shrinkage and expansion, leading to geotechnical issues, such as loss of strength. This study explored the effectiveness of the Polymer–Calcite Precipitation (PCP) method in improving clay shale's shear strength. This study evaluated the optimum Polyvinyl Alcohol (PVA) concentration for enhancing the shear strength and identifying the residual shear strength of the treated soil. Various tests were conducted to determine the soil properties and assess soil improvement using direct shear tests. The results indicate that adding PVA increases the cohesion value of saturated clay shale and maintains its residual strength close to its peak strength value, with the optimum concentration of 4% PVA boosting cohesion from 4.47 kPa to 32.83 kPa. In conclusion, the PCP method effectively enhances the shear strength of clay shale and offers a potential solution for soil stabilization.